Biodegradable polyester composition as well as preparation method and application thereof
By adding fillers, slippers, antistatic agents and surfactants to biodegradable polyester materials, the problems of impulse bonding of polyester materials in cutting bags and poor printing of water-based inks are solved, and the resistance of polyester is improved Adhesion and printing effect, suitable for the production of biodegradable plastic products.
Patent Information
- Application Number
- CN202411538102.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
Biodegradable polyester materials are prone to adhesion problems when cutting bags and punching, and the surface tension of the aqueous ink during printing is high, resulting in high unsaturation and peeling rate of pattern printing, affecting production efficiency and environmental safety.
Using a biodegradable polyester composition, including biodegradable polyester, fillers, slippers, antistatic agents and surfactants, the anti-impact adhesive properties of the polyester and ink are significantly improved by the combination of these additives. Printability and adhesion, improving the surface polarity and compatibility of polyester materials.
It significantly improves the impact adhesion resistance and ink printing properties of polyester materials, reduces adhesion phenomena, improves printing effect and adhesion, and is suitable for the preparation of biodegradable plastic films and plastic bags.
Smart Images

Figure BDA0005112077990000091 
Figure BDA0005112077990000092 
Figure BDA0005112077990000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a biodegradable polyester composition and a preparation method and application thereof. Background Art
[0002] Biodegradable polyester materials are currently widely used in the packaging industry, such as shopping bags, milk tea bags and garbage bags, but the problem of "punch adhesion" often occurs when cutting and punching the bags, affecting the consumer experience. There are currently several ways in the industry to improve the punch adhesion: first, reduce the film blowing speed to strengthen the crystallization cooling; second, leave the film for two or three days before cutting the bag; third, increase the film blowing machine to 6 meters or even 7 meters and provide strong refrigeration to the workshop; fourth, use opening agents, lubricants and antistatic agents. However, the first two methods affect production efficiency to varying degrees, the third method requires the modification of the machine, which is restricted by the workshop space and causes cost waste, and only the fourth method is simple and easy.
[0003] With the development of the industry, high-speed film blowing and lightweight thinning are the major trends in the future production of biodegradable films. Under this trend, the problem of "punching adhesion" will become more severe. On the other hand, biodegradable polyester materials are usually required to print corresponding trademarks and other contents in film bag applications. Traditional solvent-based inks contain volatile organic solvents and harmful metals, which have a strong and pungent odor. They not only seriously pollute the environment, but also seriously endanger human health. Therefore, they have gradually been replaced by water-based inks in packaging printing. However, due to the high surface tension of water-based inks, they have poor wettability and adhesion to plastic film substrates with low surface tension. Therefore, biodegradable polyester materials often have problems such as unsaturated color of pattern printing and high printing peeling rate during the printing process. Therefore, it is of great significance to develop a biodegradable polyester material that is resistant to adhesion and can be efficiently printed with water-based inks and a preparation method thereof.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a biodegradable polyester composition and a preparation method and application thereof. The biodegradable polyester composition has excellent anti-punch adhesion, water-based ink printability and adhesion.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A biodegradable polyester composition comprises the following components in parts by weight: 50 to 92 parts of biodegradable polyester, 9 to 50 parts of filler, 0.08 to 1.1 parts of lubricant, 0.08 to 1.1 parts of antistatic agent, and 0.08 to 1.1 parts of surfactant; the auxiliary agent comprises at least one of the lubricant and the antistatic agent;
[0008] The surfactant includes at least one of N,N-bishydroxyethyl alkyl amide, modified bisstearic acid amide, and stearic acid ethoxyamide wax.
[0009] The present invention creatively combines the above-mentioned raw materials, takes biodegradable polyester as the matrix, and works together with fillers, lubricants, antistatic agents and surfactants to significantly improve the anti-punch adhesion, water-based ink printability and adhesion of the composition. The biodegradable polyester composition is very suitable for preparing degradable plastic products. Due to its excellent anti-punch adhesion, water-based ink printability and adhesion, it is particularly suitable for preparing degradable plastic films and degradable plastic bags.
[0010] The applicant speculates that by adding fillers, lubricants, antistatic agents and surfactants to the biodegradable polyester matrix of the present invention, the surfactant is a surfactant containing amino, alkyl, hydroxyl, amide and / or ethoxy groups at the same time. Because it contains both lipophilic non-polar groups and hydrophilic polar groups, the lipophilic groups have good compatibility with the biodegradable polyester, and the hydrophilic groups modify the surface of the film, significantly enhancing the surface polarity of the biodegradable polyester material and increasing its surface tension, thereby significantly improving the printing effect, spreadability and adhesion of the ink on the surface of the product prepared therefrom, and effectively improving the compatibility of the system. The addition of lubricants and antistatic agents can significantly reduce the dynamic and static friction coefficients, further reduce adhesion, improve the fluidity of the polyester, avoid melt fracture, and improve the dispersibility of the filler.
[0011] The amount of the biodegradable polyester is 50 to 92 parts, for example, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 92 parts or a range consisting of any two of these values.
[0012] Preferably, the resin is used in an amount of 51 to 90 parts.
[0013] The amount of the filler is 9 to 50 parts, for example, 9 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or a range consisting of any two of these values.
[0014] Preferably, the amount of the filler is 10 to 49 parts.
[0015] The dosage of the auxiliary agent is 0.08 to 1.1 parts, for example, it can be 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts or a range consisting of any two of the values.
[0016] Preferably, the dosage of the auxiliary agent is 0.1 to 1 part.
[0017] Among them, the dosage of the surfactant is 0.08 to 1.1 parts, for example, it can be 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts or a range consisting of any two of the values.
[0018] Preferably, the amount of the surfactant is 0.1 to 1 part.
[0019] Preferably, the biodegradable polyester composition comprises the following components in parts by weight: 51 to 90 parts of biodegradable polyester, 10 to 49 parts of filler, 0.1 to 1 part of lubricant, 0.1 to 1 part of antistatic agent, and 0.1 to 1 part of surfactant.
[0020] Preferably, the biodegradable polyester composition comprises the following components in parts by weight: 70 to 80 parts of biodegradable polyester, 20 to 30 parts of filler, 0.4 to 0.8 parts of auxiliary agent, and 0.3 to 0.7 parts of surfactant. In particular, when the amount of each raw material is within this range, the anti-punch adhesion, water-based ink printability and adhesion are further improved.
[0021] Wherein, in the biodegradable polyester composition of the present invention, the weight percentage of the biodegradable polyester is not less than 48%.
[0022] Preferably, in the biodegradable polyester composition of the present invention, the weight percentage of the biodegradable polyester is 48-80%, for example, it can be 48%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two of these values.
[0023] Preferably, the lubricant includes at least one of an amide lubricant and a wax lubricant.
[0024] Preferably, the amide lubricant includes at least one of erucamide, stearic acid amide, behenic acid amide, oleic acid amide and ethylene bisstearic acid amide.
[0025] Preferably, the wax lubricant includes at least one of polyethylene wax, montan wax, oxidized polyethylene wax and rice bran wax.
[0026] Preferably, the antistatic agent includes at least one of a fatty acid ester antistatic agent, an alkyl ethoxy amine antistatic agent, and an alkyl sulfonate antistatic agent.
[0027] Preferably, the auxiliary agent includes an antistatic agent and a lubricant, and the weight ratio of the antistatic agent to the lubricant is (0:1) to (7:1).
[0028] Preferably, the auxiliary agent includes an antistatic agent and a lubricant, and the mass ratio of the antistatic agent to the lubricant is (3:5) to (5:3).
[0029] Preferably, the filler includes at least one of calcium carbonate, talc, montmorillonite, silicon dioxide and titanium dioxide.
[0030] Preferably, the average particle size of the filler is 1-10 μm, for example, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm or a range consisting of any two values therein.
[0031] The average particle size of the filler is obtained by testing according to GB / T 19077.
[0032] Preferably, the filler includes at least one of calcium carbonate and talc.
[0033] Preferably, the biodegradable polyester composition comprises a first biodegradable polyester and a second biodegradable polyester; the first biodegradable polyester is PBAT (polybutylene adipate terephthalate), and the second biodegradable polyester is at least one of PLA (polylactic acid), PBSeT (polybutylene sebacate terephthalate), and PBS (polybutylene succinate); the mass ratio of the first biodegradable polyester to the second biodegradable polyester is (50-80): (1-10).
[0034] Preferably, the weight average molecular weight of the PBAT is 90,000 to 180,000, for example, 90,000, 100,000, 120,000, 140,000, 150,000, 160,000, 180,000 or a range consisting of any two of these values.
[0035] Preferably, the PBAT is a copolymer of butylene adipate and butylene terephthalate, wherein the molar ratio of butylene adipate to butylene terephthalate is (43.5-52.0):(48.0-56.5).
[0036] Preferably, the weight average molecular weight of the PBAT is 110,000 to 150,000.
[0037] Preferably, the PBAT has a melt mass flow rate of 1 to 50 g / 10 min at 190 ° C and 2.16 kg load according to ISO 1133-2011, for example, 1 g / 10 min, 2 g / 10 min, 4 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min or a range consisting of any two of the values.
[0038] Preferably, the PBAT has a melt mass flow rate of 2 to 20 g / 10 min at 190° C. and a load of 2.16 kg according to ISO 1133-2011.
[0039] Preferably, the second biodegradable polyester is PLA, and the molar percentage of D-lactic acid in the PLA is 1 to 20%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20% or a range consisting of any two of these values.
[0040] The PLA mentioned in the present invention can be a commercially available product or homemade.
[0041] Exemplary, preparation method of PLA (homemade method):
[0042] S1. Add L-lactic acid, D-lactic acid and the first catalyst into a reaction vessel, stir evenly, and perform polycondensation reaction to obtain oligomers. Distill the obtained oligomers under reduced pressure at a temperature until no product is distilled out to obtain a lactide intermediate.
[0043] S2. The lactide intermediate obtained in the above step is dissolved in an initiator (hexanediol), a second catalyst is added, and a ring-opening polymerization reaction is carried out. The obtained polymer solid is dissolved by refluxing with a 5% (W / W) chloroform aqueous solution. After the solution is filtered, it is precipitated with ethanol 4 to 6 times the volume of chloroform to obtain a polylactic acid resin.
[0044] It should be noted that the present invention controls the molar percentage of D-lactic acid in PLA by controlling the ratio of L-lactic acid to D-lactic acid. Wherein, the first catalyst and the second catalyst include at least one of stannous octoate and dibutyltin dilaurate.
[0045] The amount of the first catalyst and the second catalyst used is not limited in the present invention, as long as it is sufficient to promote the reaction. For example, the first catalyst can be 0.05-0.5% of the total mass of the reaction monomers, and the second catalyst can be 0.05-0.5% of the mass of the lactide intermediate.
[0046] The temperature of the polycondensation reaction is 95-105°C and the time is 6-12h.
[0047] The temperature of the reduced pressure distillation is 185-195°C.
[0048] The ring-opening polymerization reaction is specifically as follows: first react at a temperature of 145-155° C. and a relative pressure of 110,000 Pa for 2-5 hours, and then react at a temperature of 175-185° C. and a relative pressure of 110,000 Pa for 1-4 hours.
[0049] Preferably, the PLA has a melt mass flow rate of 1 to 50 g / 10 min at 190 ° C and a load of 2.16 kg according to ISO 1133-2011, for example, 1 g / 10 min, 2 g / 10 min, 4 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min or a range consisting of any two of the values.
[0050] Preferably, the PLA has a melt mass flow rate of 1 to 10 g / 10 min at 190° C. and a load of 2.16 kg according to ISO 1133-2011, for example, 1 g / 10 min, 2 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 8 g / 10 min, or 10 g / 10 min.
[0051] Preferably, the biodegradable polyester composition of the present invention may further include at least one of a toughening agent, a colorant, an antioxidant, a weathering agent, a flame retardant, and an ultraviolet light absorber.
[0052] The biodegradable polyester composition of the present invention may include a toughening agent, and suitable toughening agents include but are not limited to ethylene-octene copolymer, SEBS, maleic anhydride grafted POE, maleic anhydride grafted SEBS and combinations thereof.
[0053] The biodegradable polyester composition of the present invention may include a colorant. Suitable colorants include, but are not limited to, carbon black, titanium dioxide, zinc sulfide, red iron, titanium yellow and combinations thereof.
[0054] The biodegradable polyester composition of the present invention may include an antioxidant. Suitable antioxidants include, but are not limited to, antioxidant 1098, antioxidant 1010, antioxidant 1076, antioxidant 168 and combinations thereof.
[0055] The biodegradable polyester composition of the present invention may include a weathering agent, and suitable weathering agents include but are not limited to hindered amine light stabilizers, benzotriazole ultraviolet light absorbers, and combinations thereof.
[0056] The biodegradable polyester composition of the present invention may include a flame retardant, and suitable flame retardants include but are not limited to brominated polymers (e.g., brominated polystyrene), metal dialkyl phosphites (e.g., tris(diethylphosphite)aluminum), metal hydroxides (e.g., magnesium hydroxide), aromatic phosphates (e.g., resorcinol di(diphenyl phosphate) ester and bisphenol A di(diphenyl phosphate) ester), and combinations thereof.
[0057] The biodegradable polyester composition of the present invention may include an ultraviolet light absorber. Suitable ultraviolet light absorbers include, but are not limited to, hydroxybenzophenones, hydroxybenzotriazoles, hydroxybenzotriazines, cyanoacrylates, nanoscale inorganic materials (eg, titanium oxide, cerium oxide, and zinc oxide), and combinations thereof.
[0058] The present invention also provides a method for preparing a biodegradable polyester composition, comprising the following steps:
[0059] According to the proportion, the biodegradable polyester, filler, auxiliary agent and surfactant are uniformly mixed and melt-extruded to obtain the biodegradable polyester composition.
[0060] The present invention also provides an application of a biodegradable polyester composition in the preparation of a degradable product, wherein the degradable product comprises at least one of a degradable plastic bag and a degradable plastic film.
[0061] The beneficial effects of the present invention are as follows: the present invention uses biodegradable polyester as a matrix, and the filler, lubricant, antistatic agent and surfactant work together to significantly improve the anti-punch adhesion, water-based ink printability and adhesion of the composition. The biodegradable polyester composition is very suitable for preparing degradable plastic products. Due to its excellent anti-punch adhesion, water-based ink printability and adhesion, it can effectively improve the printing effect of ink on the surface of the product prepared by it, improve the spreadability and adhesion of ink on its surface, and is particularly suitable for preparing degradable plastic films and degradable plastic bags. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0063] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0064] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0065] The raw materials used in the embodiments and comparative examples are described as follows:
[0066] PBAT-1: weight average molecular weight 150,000, Jinfa Biotechnology, brand KB100 NC801.
[0067] PBAT-2: weight average molecular weight 110,000, Jinfa Biotechnology, brand KB100 HF NC801.
[0068] PBAT-3: weight average molecular weight 180,000, Jinfa Biotechnology, brand KB100 LF NC801.
[0069] PBAT-4: weight average molecular weight 90,000, Jinfa Biotechnology, brand KB100 SF NC801.
[0070] PLA-1: D-lactic acid content 4% by mole, homemade.
[0071] PLA-2: D-lactic acid content 10% by mole, homemade.
[0072] PLA-3: D-lactic acid content 1% by mole, homemade.
[0073] PLA-4: D-lactic acid content 20% by mole, homemade.
[0074] PLA-5: D-lactic acid molar content 4%, Fengyuan Futailai, brand: FY804.
[0075] PBSeT: Kingfa Biotechnology, brand A300 NC801.
[0076] PBS: Kingfa Biotechnology, brand A200 NC801.
[0077] Filler-1: calcium carbonate, average particle size 5 μm, commonly available in the market.
[0078] Filler-2: talcum powder, average particle size 5 μm, commonly available in the market.
[0079] Filler-3: montmorillonite, average particle size 5 μm, commonly available in the market.
[0080] Filler-4: silicon dioxide, average particle size 5 μm, commonly available on the market.
[0081] Slip agent-1: erucamide, commonly available in the market.
[0082] Slip agent-2: stearic acid amide, commonly available in the market.
[0083] Slip agent-3: polyethylene wax, commonly available in the market.
[0084] Slip agent-4: montan wax, commonly available on the market.
[0085] Surfactant-1: N,N-bis(hydroxyethyl)alkylamide, commonly available on the market.
[0086] Surfactant-2: modified bis-stearic acid amide, Suzhou Xingtai Guo Photochemical Additive Co., Ltd., brand TAS-3A.
[0087] Surfactant-3: stearic acid ethoxyamide wax, commonly available in the market.
[0088] Surfactant-4: stearic acid, commonly available in the market.
[0089] Antistatic agent-1: fatty acid ester antistatic agent, Hoda, brand antistatic agent 129.
[0090] Antistatic agent-2: fatty acid ester antistatic agent, Clariant, brand HOSTASTAT FE1.
[0091] Antistatic agent-3: Alkyl ethoxylated amine antistatic agent, Hoda, brand ATMER 163.
[0092] Antistatic agent-4: Alkyl sulfonate antistatic agent, Clariant, brand name HOSTASTAT HS-1.
[0093] Wherein, the preparation methods of PLA-1 to PLA-4 all include the following steps:
[0094] S1. Add L-lactic acid, D-lactic acid and stannous octoate into the reaction vessel, stir evenly, and carry out polycondensation reaction at a temperature of 100°C and a pressure of 5KPa. After 9 hours, distill off water to obtain oligomers. Distill the obtained oligomers under reduced pressure at a temperature of 190°C and a pressure of 102Pa until no product is distilled out. The time is 11 hours to obtain a lactide intermediate.
[0095] S2. The lactide intermediate obtained in the above step is dissolved in hexylene glycol, and stannous octoate is added to carry out a ring-opening polymerization reaction, specifically: first react at a temperature of 150° C. and a relative pressure of 110,000 Pa for 4 hours, and then react at a temperature of 180° C. and a relative pressure of 110,000 Pa for 2.5 hours to obtain a polymer, and the obtained polymer solid is refluxed and dissolved with a 5% (W / W) chloroform aqueous solution. After the solution is filtered, it is precipitated with ethanol 5 times the volume of chloroform to obtain PLA.
[0096] The molar percentage of D-lactic acid in PLA can be controlled by controlling the molar ratio of L-lactic acid to D-lactic acid.
[0097] The testing standards for raw material parameters are as follows:
[0098] The content of D-lactic acid in polylactic acid can be determined by the following method: pure L-lactic acid and pure D-lactic acid are tested by gas chromatography to obtain the peaks of the two; under the same test conditions, the target polylactic acid is tested, and the peak areas δ of the corresponding L-lactic acid and D-lactic acid peaks on the gas chromatogram are obtained. L and δ D , the content of D-lactic acid in the target polylactic acid is calculated, and the calculation formula is: η=δ D / (δ L +δ D )*100%.
[0099] Among them, gel chromatography is used to test the weight-average molecular weight of polyester, as follows: the polyester is dissolved in tetrahydrofuran, and analyzed by Waters2410 gel chromatograph from Waters Company of the United States, with a column temperature of 25°C, tetrahydrofuran as solvent and eluent, a flow rate of 1.0 mL / min, polystyrene as the standard sample for the calibration curve, and a retention time of 50 min.
[0100] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0101] Examples 1 to 31, Comparative Examples 1 to 2
[0102] The formulations of the biodegradable polyester compositions of Examples 1 to 31 and Comparative Examples 1 to 2 are shown in Table 1 and Table 2 (all in the tables are parts by weight).
[0103] The preparation methods of the biodegradable polyester compositions of Examples 1 to 31 and Comparative Examples 1 to 2 all include the following steps:
[0104] According to the ratio, the biodegradable polyester, filler, auxiliary agent and surfactant are uniformly mixed and melt-extruded through a twin-screw extruder. The twin-screw extruder has a screw diameter of 75 mm, an aspect ratio of 52 and a processing temperature of 160-200° C. to obtain a biodegradable polyester composition.
[0105] Table 1
[0106]
[0107] Table 2
[0108]
[0109]
[0110] Performance Testing
[0111] Film preparation: The obtained biodegradable polyester composition was put into a film blowing machine and film was blown at 150-160° C., a screw speed of 25 Hz, a traction speed of 10 m / min, and a blow-up ratio of 3. The film thickness was 50 μm.
[0112] 1. Surface tension test method: Use a dyne pen with a dyne value range of 26-44 for testing.
[0113] 2. Printing peeling rate test method: Test in accordance with GB / T 38082-2019. With the printed surface of the sample facing up, use transparent tape to fix the sample on a smooth table to expose the test area: 100mm×100mm. Do not touch the measuring area with your hands during the operation. Use an adhesive tape with a 180° peel strength of 6.5N / 15mm±1.0N / 15mm, take a width of 15mm and a length of 175mm and stick it on the printed surface of the sample. Fold it 180° at 75mm, and roll it back and forth once with a 1kg roller at the pasting area. Then peel it off quickly by hand. After peeling, use a steel ruler with a graduation value of 0.5mm to measure the peeling area and residual area of the printing ink, and calculate the printing peeling rate according to the following formula. Take 3 samples, take the average value, and round off the result to 1%.
[0114]
[0115] Where: η is the printing peeling rate; Sb is the peeling area; Sc is the residual area.
[0116] 3. The criteria for determining the level of punching adhesion are shown in Table 3.
[0117] Table 3
[0118] grade definition describe N1 No adhesion The punching mouth spreads naturally, the membrane surface is not damaged, and no external force is required N2 Slight adhesion It will be dispersed by rubbing lightly with hands, the film surface is not damaged, and only slight external force is needed N3 Medium adhesion It can be spread by rubbing and pulling, and the film surface is not damaged, but a large external force is required N4 Obvious adhesion It can be separated by rubbing and pulling, but the edge of the film is damaged and requires a large external force N5 Severe adhesion Completely adhered and cannot be separated, and the membrane surface is obviously damaged by external force
[0119] Table 4
[0120]
[0121]
[0122] As can be seen from Table 4, the biodegradable polyester composition of the present invention has excellent anti-punch adhesion, ink printability and adhesion, can effectively improve the printing effect of ink on the surface of the product prepared therefrom, and is particularly suitable for preparing degradable plastic films and degradable plastic bags. The dyne value of the biodegradable polyester composition of the present invention is ≥34, the printing peeling rate is ≤8%, and the punch adhesion grade is ≤N2.
[0123] By comparing Examples 2 and 5 to 7, it can be seen that the present invention further improves the anti-punch adhesion and printing peeling rate by controlling the weight average molecular weight of PBAT to 110,000 to 150,000.
[0124] Comparative Examples 2 and 18 to 20 show that the present invention uses an amide lubricant to further improve the anti-punch adhesion, printing peeling rate and dyne value.
[0125] By comparing Examples 2 and 26 to 31, it can be seen that the present invention uses an antistatic agent and a lubricant as auxiliary agents in a weight ratio of (3:5) to (5:3), which further improves the anti-punch adhesion, printing peeling rate and dyne value.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A biodegradable polyester composition, characterized in that The invention comprises the following components in parts by weight: 50 to 92 parts of biodegradable polyester, 9 to 50 parts of filler, 0.08 to 1.1 parts of auxiliary agent, and 0.08 to 1.1 parts of surfactant; The auxiliary agent includes at least one of a lubricant and an antistatic agent; The surfactant includes at least one of N,N-bishydroxyethyl alkyl amide, modified bisstearic acid amide, and stearic acid ethoxyamide wax.
2. The biodegradable polyester composition according to claim 1, characterized in that The lubricant comprises at least one of an amide lubricant and a wax lubricant; and / or The antistatic agent includes at least one of a fatty acid ester antistatic agent, an alkyl ethoxy amine antistatic agent, and an alkyl sulfonate antistatic agent.
3. The biodegradable polyester composition according to claim 2, characterized in that The amide lubricant includes at least one of erucamide, stearamide, behenamide, oleamide, and ethylene bisstearamide; and / or The wax lubricant includes at least one of polyethylene wax, montan wax, oxidized polyethylene wax and rice bran wax.
4. The biodegradable polyester composition according to claim 1, characterized in that The auxiliary agent comprises an antistatic agent and a lubricant, and the weight ratio of the antistatic agent to the lubricant is (0:1) to (7:1).
5. The biodegradable polyester composition according to claim 1, characterized in that: The filler includes at least one of calcium carbonate, talc, montmorillonite, silicon dioxide and titanium dioxide.
6. The biodegradable polyester composition according to claim 1, characterized in that: The biodegradable polyester includes a first biodegradable polyester and a second biodegradable polyester; the first biodegradable polyester is PBAT, and the second biodegradable polyester is at least one of PLA, PBSeT, and PBS; the mass ratio of the first biodegradable polyester to the second biodegradable polyester is (50-80):(1-10).
7. The biodegradable polyester composition according to claim 1, characterized in that: The weight average molecular weight of the PBAT is 90,000 to 180,000.
8. The biodegradable polyester composition according to claim 6, characterized in that: The second biodegradable polyester is PLA, and the molar percentage of D-lactic acid in the PLA is 1-20%.
9. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the proportion, the biodegradable polyester, filler, auxiliary agent and surfactant are uniformly mixed and melt-extruded to obtain the biodegradable polyester composition.
10. Use of the biodegradable polyester composition according to any one of claims 1 to 8 in the preparation of degradable products, characterized in that: The degradable product includes at least one of a degradable plastic bag and a degradable plastic film.
Citation Information
Cited By
Biodegradable film material as well as preparation method and application thereof
CN119875324A
Biodegradable film material, and preparation method therefor and use thereof
WO2026158000A1